Business Feasibility Analysis in the Dodol Pineapple Agroindustry in Jalancagak District, Subang Regency - Aulia, Rieke Gaby; Yusiana, Ekalia; Syahputra, Ali Fahmi (Peneliti.net, 2025)
Jalancagak District is the only district that produces the highest pineapple fruit in Subang Regency. The pineapple dodol agroindustry in Subang Regency in its marketing has problems, namely the lack of promotion and distribution of products by pineapple dodol entrepreneurs which causes marketing to be limited, sales tend to fluctuate so that the business is not developing well. Pineapple dodol is one of the processed pineapple fruit mixed with sticky rice flour, sugar, coconut milk, and other ingredients. This study has the following objectives: (1) To analyze the costs, revenues, and income of the pineapple dodol agroindustry in Jalancagak District, Subang Regency. (2) To determine the feasibility of the pineapple dodol agroindustry business in Jalancagak District, Subang Regency. The research method used is quantitative and qualitative descriptive research. In this study, the researcher determined 10 people as respondents using the Saturated Sampling method (census). The results of the study showed that: (1) The average variable cost is IDR 8,139,500/month. The average fixed cost is IDR 1,287,063/month. So the average total production cost is Rp. 9,426,563/month. The average total income is Rp. 16,775,000 with an average production quantity of 305 kg/month and an average selling price of Rp. 55,000/kg. The average pineapple dodol income is Rp. 7,348,437/month (2) The BEP value of pineapple dodol production is 43 kg/month. The BEP price is Rp. 430.907/kg. BEP income from sales is Rp. 2,337,844/month. (3) The results of the R/C Ratio calculation obtained a value of 1.78. This states that all pineapple dodol entrepreneurs > 1, meaning that the pineapple dodol agroindustry in Jalancagak District, Subang Regency is declared to be run and cultivated.